PENGARUH EMULGATOR BUAH LERAK (sapindus rarak) DENGAN EMULSI AIR DAN SOLAR SEBAGAI BAHAN BAKAR MOTOR DIESEL RAMAH LINGKUNGAN - Ismail Ismail; Dwi Nova; Nova Suparmanto; Dwi Rahayu; Rusliyanto Rusliyanto (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This research is aimed at finding out the effect of emulsion of water and diesel fuelwith lerak emulsifier on the gas emission of diesel fuel and its effect on the power producedby the diesel motor.The steps involved in the research are extracting lerak and blending the emulsion ofwater and diesel fuel by using lerak extract emulsifier. To test the sample of lerak extractmethods used were IKU/5.4/TK-02 for Viscosity Kinematic at 30°C, IKU/5.4/TK-03 for FlashPoint PM.CC, IKU/5.4/TK-04 for Pour Point, ASTM 130 for Copperstrip Corosion at 100°C, (3hrs),ASTM 473 for Sediment test, dan ASTM D 95 for Water Content.The reasearch result showed that the lerak extract was made successfully by usingethanol solvent. However, the process of blending the lerak emulsifier and water as well asdiesel fuel was not successful yet. They were not blended perfectly yet though the result ofthe blending process had shown the different contents of diesel fuel.Keywords: emulsifier, lerak fruit, water emulsion, diesel engine